Inflammation in Right Ventricular Failure: Does It Matter? - Dewachter, Laurence; Dewachter, Céline (Frontiers in Physiology, 2018)
Right ventricular (RV) failure is a commonnly seen as a consequence of acute and chronic RV RV pressure overload of pressure, such as after pulmonary embolism and pulmonary hypertension. It has been recentlybetter realized in recent years that symptomatology and survival of patients with pulmonary hypertension are essentially determined by RV function adaptation to increased afterload. Therefore, improvement of RV function and reversal of RV failure are treatment goals. Currently, the pathophysiology and the pathobiologygic mechanisms involved inunderlying RV failure remain largely unknown. A better understanding of the pathophysiological processes involved in RV failure is needed, as there is no proven treatment for this disease at the moment. The purpose of thise present review aims is to summarize the current understanding of the pathogenesisphysiology and the pathobiology of RV failure, focusing on inflammation. We attempt to formally emphasize the importance of inflammation and associated representative inflammatory molecules and cells in the primum movensgenesis and development of RV failure in humans and in experimental models. We present inflammatory biomarkers and immune mediators involved in RV failure. We focus on inflammatory mediators and cells which seem to correlate with the deterioration of RV function and also explain how all these inflammatory mediators and cells might impact RV function adaptation to increased afterload. Finally, we will also discuss the evidence on potential beneficial effects of targeted anti-inflammatory agents in the setting of acute and chronic RV failure.